.detecting CD103 cells in the skin of smoking psoriatic patients compared to non-smoking ones - حرفوش, نورا; حسن, فوز; اسماعيل, محمد عادل; داؤد, علي (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Despite the association of the pathological mechanism of psoriasis with immune changes in the late 1970s, a major shift in understanding the pathogenesis of psoriasis followed the discovery of the role of anti-T agent such as cyclosporine in improving the clinical condition of patients. Based on this, psoriasis has been considered a T-cell-mediated disease in the last two decades. The widespread prevalence of this disease in our region and the difficulty of treating it in a way that satisfies the patient makes it necessary to continue research into its pathological mechanisms in the hope of finding more effective, qualitative and sustainable treatment methods. Materials and Methods: Our study included 8 recent psoriasis patients from the Dermatology Clinic at Tishreen University Hospital. Immunostaining was performed for memory T cells formed after effective attack healing, and the sample was divided according to habits and instincts into two subgroups: smokers and non-smokers, with the aim of comparing CD103 memory cell counts between the two groups. Results: Our study, conducted at Tishreen University Hospital, found no statistically significant differences between the two groups in terms of the number of CD103 memory cells, which are implicated in the direct role in psoriasis plaque relapses. Conclusions and Recommendations: Given the proven negative relationship between smoking and psoriasis in many international scientific studies, it is necessary to delve deeper into studying the effect of smoking in a more accurate and direct manner, taking into account the presence of a larger sample size and comparing it with the evidence.